Posidonius as a Possible Source of Diodorus’ Description of the Dead Sea (Diod. 2. 48. 6–8; 19. 98–99) - Starikova, Arina (Hyperboreus, 2022)
The name Asphalt Lake (ἡ Ἀσφαλτῖτις λίμνη) for the Dead Sea is first attested in Diodorus (Diod. 19. 98. 1), who describes the lake twice in almost identical passages (2. 48. 6–8 and 19. 98–99). It is remarkable that this name occurs in the second passage (19. 98–99) and at the same time the Dead Sea remains unnamed in the first description. The name Asphalt Lake is likely enough to have been coined by Diodorus himself and not borrowed by him from another source. Hieronymus of Cardia, the author of the History of Diadochi, whom Antigonus entrusted to control the asphalt extraction, is a generally accepted source for Books 18–20 of Diodorus’ Bibliotheca Historica (19. 100). However, the description of the Dead Sea in 19. 98 could not go back only to Hieronymus (FGrHist 154 F 5). Rare details (such as metals tarnishing caused by the lake vapors and the seismicity of the Dead Sea region) and the common order of characteristics suggest that Diodorus received information about the Dead Sea also from Posidonius, the extract of whose On the Ocean on the Dead Sea was preserved by Strabo (16. 2. 42–44 = FGrHist 87 F 70). Diodorus could use two sources at the same time, supplementing Hieronymus’ testimony, which was the basis of the first extract about the lake, with Posidonius’ information, added to the description in the second passage.